Intact B-Cell Signaling and Function With Host B-Cells 47 Years After Transplantation for X-SCID - Deal, Christin; Thauland, Timothy J.; Stiehm, E. Richard; Garcia-Lloret, Maria I.; Butte, Manish J. (Frontiers in Immunology, 2020)
Introduction Severe Combined Immunodeficiency (SCID) is a life-threatening immunodeficiency caused by several pathogenic genetic variants and characterized by profound defects in T-cell numbers and immune function. First performed in the late 1960s, hematopoietic stem cell transplantation remains the standard treatment for most cases of SCID. There is a growing number of post-transplant SCID patients and it is imperative to assess long-term outcomes of these patients. We report the longest follow-up of a post-transplant SCID patient who, to our knowledge, bears the first gamma chain (γc) variant to show intact IL-21 signaling. Case Presentation The patient presented at 5 months of age with recurrent thrush and Pneumocystis jiroveci pneumonia. He received an unconditioned, matched, related donor transplant at 11 months of age in 1971 comprising whole, unprocessed bone marrow. He is now 48 years old without significant illness and has never required immunoglobulin replacement. He makes T-dependent vaccine responses. He does suffer from chronic warts and bacterial infections that have worsened in recent years. We confirmed a known pathogenic variant in the IL2RG gene showing a hemizygous variant NM_000206.2:c.675C>A resulting in p.Ser225Arg. His chimerism studies revealed donor T cells, host B cells, host myeloid cells, and mixed NK cells. Lymphocyte enumeration revealed normal numbers and distribution of B cells. Host B cells carry the pathogenic variant in IL2RG, but when stimulated with IL-21 demonstrated intact, γc-dependent signaling. Conclusions Even with host B cells, reconstitution with donor T cells can be sufficient to allow over four decades of survival when B-cell function is intact. Our case demonstrates that satisfactory B-cell function can arise as a consequence of both intact IL-21 signaling due to a hypomorphic γc variant, and close HLA matching with the donor to allow for effective T-cell help.